Interaction between two independent CNR1 variants increases risk for cocaine dependence in European Americans: A replication study in family-based sample and population-based sample - Zuo, Lingjun (2008)
We recently reported that, in a European-American (EA) sample, the interaction between two cannabinoid receptor 1 gene (CNR1) variants significantly increased risk for drug dependence (DD), including cocaine dependence (CD). The present study aimed to investigate directly the association between CNR1 and CD in four independent samples. Eight markers across the 45kb CNR1 region and four large samples, i.e., family-based European-American (EA) sample (n=734), case-control EA sample (n=862), family-based African-American (AA) sample (n=834) and case-control AA sample (n=619) were examined in the present study. We investigated the association of these markers with CD and cocaine-induced paranoia (CIP) in the EA family sample first, and then replicated positive results in the other three samples. The interaction between two independent CNR1 variants, i.e., the G allele-containing genotypes of rs6454674 (SNP3^G(+)), and the T/T genotype of rs806368 (SNP8^T/T), significantly increased risk for CD in the EA family (P(GEE)=0.015) and EA case-control (P(regression)=0.003) samples. EA subjects with SNP3^G+ and SNP8^T/T had higher risk to develop CD than those EA subjects with the other genotypes for these two SNPs (LR(+)=1.4). The SNP3^G-SNP8^T haplotype also showed significant association (P=0.018) with CD in the EA case-control sample. SNP8-containing haplotypes showed significant association with both CD (P(global)=0.007) and CIP (P(global)=0.003) in the EA family sample. In the AA family sample, SNP8^T/T significantly confered higher risk for CD (P=0.019). We conclude that wo independent CNR1 variants have significant interaction effects on risk for CD in EAs; they may also have effects on risk for CD in AAs.